Development of TiO2 electrical insulation coating on Ag-alloy sheathed Bi2Sr2CaCu2O8−x round-wire. (2nd February 2015) - Kandel, H; Lu, J; Jiang, J; Chen, P; Matras, M; Craig, N; Trociewitz, U P; Hellstrom, E E; Larbalestier, D C
Abstract: We have developed TiO2 coating on Ag-alloy sheathed Bi2 Sr2 CaCu2 O8− x (Bi-2212) round-wire conductor for electrical insulation in Bi-2212 magnets. The green coating has a base layer comprised of TiO2, polyvinyl butyral (PVB) and a small amount of polysilicate and a top layer made of polyacrylic. The coating was applied on the conductor using a continuous reel-to-reel dip coating process and showed very good adherence and flexibility that is suitable for magnet coil winding. The thickness of the coating is a function of slurry viscosity, wire withdrawal speed and wire radius. Small test coils were built with the coated Bi-2212 round-wires and were heat treated at 100 atm pressure. During the heat treatment, the PVB and polyacrylic were removed from the green coating and the polysilicate decomposed to SiO2 that served as a sintering aid for TiO2 . After the heat treatment, the coating remained strongly adhered to the conductor and did not have a detrimental effect on the critical current ( I c ) values. The breakdown voltage was about 150 V across a 7 μ m thick heat treated coating on Bi-22112 round-wire conductor, corresponding to a dc dielectric strength of about 21 MV m −1 .